Immune response induced by the recombinant novel coronavirus vaccine (Adenovirus type 5 vector) (Ad5-nCoV) in persons living with HIV (PLWH) - Pedro Cahn; Luis Barreto; Maria Ines Figueroa; Valeria Fink; Maria Jose Rolon; Gustavo Lopardo; Isabel Cassetti; Mariela Ceschel; Patricia Patterson; Luciana Gambardella; Gissella Mernies; Agustin Nava; et al. (PLoS ONE, 2025)
Background Despite higher risk of poorer outcomes and potential sub-optimal vaccine effectiveness, people living with HIV (PLWH) are underrepresented in SARS-CoV-2 vaccine trials. We evaluated the safety and immunogenicity of the Ad5-nCoV vaccine (CanSino Biologics Inc./The Beijing Institute of Biotechnology) in PLWH. Methods In this single arm, open-label Phase 2b trial, PLWH were enrolled in Argentina. Participants received two doses of Ad5-nCoV vaccine (intramuscular, dosage 5x10 10 viral particles) at days 0 and 56. The primary outcomes were safety as serious adverse events [SAE], solicited and unsolicited local and systemic adverse events, impact on HIV viral load and CD4 counts and immunogenicity measured by S-RBD IgG and pseudo-virus neutralizing antibodies (nAbs) up to 52 weeks (ClinicalTrials.gov:NCT05005156). Findings Between June 2021-January 2022, 140 PLWH received at least one dose of Ad5-nCoV vaccine. At baseline, the majority were on antiretroviral therapy (99.3%), virologically suppressed (93.6%), with a median (IQR) CD4-cell count:736 (531–946) cells/ul. At baseline, 38 (27%) participants were seropositive for S-RBD antibodies, and 40 (28%) for nAbs. There were no SAEs related to the vaccine. Solicited AE within 7 days after first and second dose occurred in 93 (69%) and 75 (60%) participants, mostly grade 1, included pain, drowsiness and headache. The incidence of unsolicited AE within 28 days of vaccination was 10.7%. There were no significant changes in plasma viral load, CD4 count, CD4/CD8 ratio and no new AIDS-defining illnesses were reported. There were significant increases in the geometric mean titers (GMT) of S-RBD and nAbs between baseline to week 52. Seroconversion rates 28 days after the first and second doses (day 84) were 80% and 94% for S-RBD, and 35% and 78% for nAbs. Interpretation The Ad5-nCoV vaccine was safe and induced an adequate immune response in virologically suppressed PLWH, maintaining high antibody titers at least during the first year post-vaccination. No significant changes were observed in plasma viral load, CD4 count and CD4/CD8 ratio